2014
DOI: 10.3892/ol.2014.2239
|View full text |Cite
|
Sign up to set email alerts
|

Matrigel induces L-plastin expression and promotes L-plastin-dependent invasion in human cholangiocarcinoma cells

Abstract: The function of the extracellular matrix (ECM) in the tumor microenvironment is not limited to forming a barrier against tumor invasion. As demonstrated in pathological specimens, cholangiocarcinoma samples exhibit an enrichment of the ECM surrounding the tumor cells. In this study, we examined involvement of the ECM in the regulation of the invasiveness of cholangiocarcinoma cells. The RMCCA1 cholangiocarcinoma cell line was cultured in culture plates either with or without a coating of reconstituted ECM base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…Our data are consistent with the previous studies of PRDX4, overexpression of which was identified in many cancer types [53], including breast [54] and prostate [52], [55]. Based on the L-plastin role in tumor cell invasiveness [17], [45], [56], [57], [58], [59], [60], it was proposed to be used as a diagnostic marker [19], [61]; prognostic marker [62]; or a therapeutic target [60], [63], [64]. Our data demonstrate that extracellular L-plastin and PRDX4 have a specific role in stimulating osteoclastogenesis and thus promoting osteolysis during cancer metastasis to bone and suggest that information regarding the expression of these proteins may be particularly useful in cancers with frequently bone metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are consistent with the previous studies of PRDX4, overexpression of which was identified in many cancer types [53], including breast [54] and prostate [52], [55]. Based on the L-plastin role in tumor cell invasiveness [17], [45], [56], [57], [58], [59], [60], it was proposed to be used as a diagnostic marker [19], [61]; prognostic marker [62]; or a therapeutic target [60], [63], [64]. Our data demonstrate that extracellular L-plastin and PRDX4 have a specific role in stimulating osteoclastogenesis and thus promoting osteolysis during cancer metastasis to bone and suggest that information regarding the expression of these proteins may be particularly useful in cancers with frequently bone metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…The RMCCA1 cells, a cholangiocarcinoma cell line, cultured with a coating of Matrigel are more invasive than cells maintained in Matrigel-free plates. The protein expression profile indicated that the expression of the actin-binding protein L-plastin is upregulated by Matrigel, and the subsequent loss-of-function study, using siRNA, demonstrated that the knockdown of L-plastin reduces cell invasion induced by Matrigel (44). Vimentin, an intermediate filament protein type, is associated with a high degree of invasiveness (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, aberrant L-plastin expression is a hallmark of cancer [ 15 ]. Experimental activation of L-plastin can enhance the proliferation, invasiveness and lethality of tumor cells both in vivo and in vitro , whereas suppression can reverse these characteristics [ 16 – 22 ]. Because of its limited expression in normal cells and mechanistic role in many malignancies, L-plastin has been frequently studied as a cancer diagnostic marker [ 23 ], prognostic marker [ 24 ], or therapeutic target [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%